Peningkatan Kompetensi Profesional Guru Muhammadiyah melalui Pendampingan Lesson Study Berbasis Forum Guru Muhammadiyah di Kota Palembang: Muhammadiyah Teacher Professional Competency Improvement through Lesson Study Assistance Based on the Muhammadiyah Teacher Forum in Palembang City - Haryadi, Haryadi; Fadillah, Etty Nurmala; Kharisma, Selvia; Habibullah, Habibullah; Gunawan, Wahyu; Fadhilah, Farah Kansha (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community service aims to improve the professional competence of Muhammadiyah teachers through mentoring lesson study with the stages of plan, do, and see. This competency improvement is needed because the quality of teachers in Palembang, especially Muhammadiyah teachers, still needs to be considered higher due to the lack of training to improve teacher competence. The newly formed Muhammadiyah Teacher Forum can be a place to make this happen. This community service activity is carried out offline and online, namely offline during the debriefing of lesson study materials and online during monitoring and discussion of the implementation of activities. The results of community service activities based on monitoring results found problems at each stage of lesson study (plan, do, see) that have been given solutions. Based on the results of the evaluation, the problems experienced by teachers are becoming less and less and Muhammadiyah teachers in the city of Palembang routinely conduct lesson study discussions through the Muhammadiyah teacher forum.